Lost in Development: Unveiling the Complexity of Fatal Neural Tube Abnormalities - A Preventable Tragedy - Lema, Alemayehu Shiferaw; Suleyman, Jemila Salih; Raga, Amanuel Oljira; Sekar, Suresh Kumar Rajamani (Medical Research and Its Applications Vol. 7, 2024)
Neural tube defects (NTDs) are serious birth defects that affect the central nervous system. They occur due to a disruption in the normal development of the nervous system during embryogenesis. Although largely preventable, they are the second most common type of human congenital abnormality and pose a significant threat to global morbidity, disability, mortality, and financial expenses. According to estimates from 2015, approximately 260,100 newborns around the world are born annually with NTDs, excluding early spontaneous fetal losses. Additionally, there were an estimated 117,100 NTD-affected pregnancies that ended in stillbirth or elective terminations of pregnancy for fetal anomalies. Of the NTD-affected live births, approximately 117,900 resulted in under five deaths. The disability-adjusted life years from NTDs exceed 8.6 million. NTDs have both environmental and genetic causes. Folic acid supplementation during the periconceptional period is a well-known primary prevention method, but its implementation lags behind the knowledge about prevention. However, NTDs have been neglected and have recently become the subject of limited research. Furthermore, surveillance efforts for NTDs continue to be insufficient, with high prevalence rates persisting worldwide. Robust surveillance data are essential for the prevention and monitoring of NTDs. This chapter provides an updated discussion on the epidemiology, embryology, risk factors, diagnosis, associated defects, management, surveillance, and prevention strategies of NTDs, with a particular emphasis on lethal NTDs. Furthermore, to illustrate the clinical presentation of lethal NTDs, this chapter includes case presentations of different types of lethal NTDs with typical associated defects in singleton and multiple pregnancies that resulted in stillbirth.